Kemampuan Koneksi Matematis ditinjau dari Kemandirian Belajar Siswa pada Materi Teorema Phytagoras di Kelas VIII Mts Ushuluddin Singkawang - Ribut Sanjaya; Rika Wahyuni; Nurul Husna (Asosiasi Riset Ilmu Pendidikan Indonesia, 2024)
This study aims to: 1) describe the mathematical connection ability viewed from high learning independence; 2) to describe students' mathematical connection ability viewed from moderate learning independence, 3) to describe students' mathematical connection ability viewed from low learning independence. This research method is a descriptive method with a qualitative research type. The subjects in this study were 30 students of grade VIII. The objects in this study were students' mathematical connection ability and learning independence on the Pythagorean theorem material. Data collection instruments in the form of written tests in the form of descriptions according to indicators of mathematical connection ability, learning independence questionnaires and interviews that have been tested with content validity, construct validity, reliability, level of difficulty and discriminatory power. The overall results of the study indicate that the level of learning independence and mathematical connection ability of grade VIII students at MTs Ushuludin Singkawang on the Pythagorean theorem material is in the moderate category. While specifically showing that: 1) for students' mathematical connection ability reviewed from high independence, the average category is medium, namely 2.33 with an average value of 77.7. 2) for students' mathematical connection ability reviewed from moderate learning independence, the average category is medium, namely 2.20 with an average value of 73.85. 3) for mathematical connection ability reviewed from low learning independence, the average category is medium, namely 2.37 with an average value of 79.16.